2006
DOI: 10.1016/j.cardiores.2006.01.023
|View full text |Cite
|
Sign up to set email alerts
|

MitoKATP channel activation suppresses gap junction permeability in the ischemic myocardium by an ERK-dependent mechanism

Abstract: Opening of the mitoKATP channel activates ERK1/2 via free radicals and induces ERK-mediated suppression of GJ permeability. This suppression of GJ permeability may partly contribute to cardioprotection afforded by mitoKATP channel activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
4
36
0
1
Order By: Relevance
“…Sprague-Dawley rats of 8ϳ10 wk of age were anesthetized by pentobarbital sodium (40 mg/kg ip injection), intubated, and mechanically ventilated with a Harvard rodent ventilator using oxygen supplement. Hearts were excised, quickly mounted on a Langendorff apparatus, and perfused with modified KrebsHenseleit buffer as previously reported (20,21). Perfusion pressure and temperature of the perfusate were maintained at 75 mmHg and 38°C, respectively.…”
Section: Experiments I: Ip-immunoblotting Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sprague-Dawley rats of 8ϳ10 wk of age were anesthetized by pentobarbital sodium (40 mg/kg ip injection), intubated, and mechanically ventilated with a Harvard rodent ventilator using oxygen supplement. Hearts were excised, quickly mounted on a Langendorff apparatus, and perfused with modified KrebsHenseleit buffer as previously reported (20,21). Perfusion pressure and temperature of the perfusate were maintained at 75 mmHg and 38°C, respectively.…”
Section: Experiments I: Ip-immunoblotting Experimentsmentioning
confidence: 99%
“…IP of Cx43 and immunoblotting for kinases were performed as in our previous studies (20,21). In brief, tissues were homogenized in ice-cold Tris buffer containing 20 mM Tris ⅐ HCl, 1 mM EGTA, 5 mM NaN 3, 50 mM NaCl, 1 mM phenylmethylsulfonyl fluoride (PMSF), 50 mM Na3VO4, and a protease inhibitor cocktail (Complete Mini; Roche Diagnostics, Manheim, Germany).…”
Section: Experiments I: Ip-immunoblotting Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alteration in the expression level and spatial distribution of Cx43 in the hypertrophic myocardium suggests that this protein is influenced by ventricular remodeling (18). Naitoh et al (26) proposed that the mitoK ATP channel was one of the mechanisms regulating GJ permeability, thus leading to cardioprotective effects against ischemia. Previous studies have reported that decreasing Cx43 expression in the myocardium results in high susceptibility to arrythmogenesis (18,25).…”
Section: A B C D Ementioning
confidence: 99%
“…There is even less information available as concerns the relationship between ROS, mitoK ATP channels and arrhythmias. It is suggested that the antiarrhythmic effect of the opening mitoK ATP channels involves the ROS activated ERK pathway which reduces gap junction permeability by the phophorylation of connexin 43 [66]. Although in a previous study we have found that in anaesthetised dogs the administration of ROS scavenging N-2-mercaptopropionylglycine did not modify the antiarrhythmic effect of PC [60], the role of ROS in the PC-induced cardioprotection cannot be ruled out.…”
Section: The Role Of Reactive Oxygen Species In Preconditioningmentioning
confidence: 95%